Analisis Metode Penerapan Strategi Bercerita Untuk Meningkatkan Motivasi Dan Pemahaman Konsep Pembelajaran - Lutfil Amin; Moch. Fauzi; Mathori Mathori; Nasiruddin Nasiruddin; Miftahus Surur; Ahmad Hafas Rasyidi (CV. Aksara Global, 2024)
The background of this research is the low literacy culture of students, this can be seen from the reading interest of Indonesian children which is still relatively low. According to a UNESCO survey, Indonesian children only read 27 pages a year and the dominant reading time of around 0-2 hours per day is 63%, while reading longer than 6 hours per day is only 2%. The purpose of this study was to find out the application of the storytelling method in increasing children's literacy in Indonesian language subjects. This study used descriptive qualitative research, while data collection techniques were carried out through interviews and observation. The results of this study indicate that literacy has a broad scope, not only talking about reading and writing letters, but the ability to capture information with logical and critical thinking, which is ultimately able to use it effectively to achieve certain goals. One method of increasing literacy in children is the storytelling method. The conclusion of this study is that there is a change in verbal ability, creativity and critical thinking in contributing ideas and imagination in the classroom.